Pengembangan Media Pembelajaran Permainan Monopoli Untuk Meningkatkan Penguasaan Materi Alat-Alat Optik - Sabono, Rosina Elsye; Nirahua, Juliana; Sapulete, Heppy (Physikos: Journal of Physics and Physics Education, 2023)
This research is research and development (R&D) to develop a monopoly game media on optical devices materials. The flow of the development method is adapted from the Four-D development method (Define, Design, Develop, Disseminate) whose implementation only reaches the develop stage. The monopoly game media developed has been tested for feasibility by experts so that it is suitable for use to improve mastery of optical devices material in grade VIII students of Kartika Ambon junior high school. The results of the limited trial obtained an average initial ability of students of 37.5 with failed qualifications and the average formative score of students after the learning process using monopoly game media was 85.75 with good qualifications. The results of the gain test showed an increase in mastery of optical devices material in grade VIII students of Kartika Ambon junior high school with an average gain value of 0.77 in the high category. Thus, the monopoly game learning media developed can increase the mastery of optical devices material in grade VIII students of Kartika Ambon junior high school.